2010
DOI: 10.1038/jid.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

Acrosyringium Is the Main Site of the Vesicle/Pustule Formation in Palmoplantar Pustulosis

Abstract: Pustulosis palmaris et plantaris or palmoplantar pustulosis (PPP) is a refractory pustular eruption on the palms and soles with unknown etiology. Numerous eccrine sweat pores exist on the palms and soles, suggesting the involvement of eccrine sweating in the pathogenesis of PPP. To the best of our knowledge, however, no definite abnormality in sweating has been documented in PPP. Accordingly, we analyzed the eccrine sweat duct involvement in the mechanism of vesicle formation in PPP. Dermatoscopy showed that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 32 publications
2
68
0
3
Order By: Relevance
“…This suggested that the eosinophilic pustules on the palms and soles in the EPF were anatomically correlated with the eccrine apparatus. Similar findings have been demonstrated in neutrophilic pustules of palmoplantar pustulosis (3). Although eosinophilic infiltration to the dermal eccrine ducts and glands was not seen, intraepidermal eccrine ducts may be the sites predominantly affected by the palmoplantar lesions of EPF.…”
Section: Discussionsupporting
confidence: 61%
“…This suggested that the eosinophilic pustules on the palms and soles in the EPF were anatomically correlated with the eccrine apparatus. Similar findings have been demonstrated in neutrophilic pustules of palmoplantar pustulosis (3). Although eosinophilic infiltration to the dermal eccrine ducts and glands was not seen, intraepidermal eccrine ducts may be the sites predominantly affected by the palmoplantar lesions of EPF.…”
Section: Discussionsupporting
confidence: 61%
“…Sweat significantly stimulates the production of IL-8, a cytokine that can recruit neutrophils. Several reports show that IL-8 is essential for recruiting neutrophils to the lesional skin in palmoplantar pustulosis [21], [22]. It seems that lesional or systemic IL-8 increases may contribute to the pathogenesis of pustular skin lesions of neutrophilic dermatosis.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is specifically and constitutively expressed in the sweat glands and secreted into sweat . Murakami et al . studied the sweat secretion in the pathomechanism of palmoplantar pustulosis by using dermcidin as a marker for sweat.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, immunohistochemical staining of dermcidin (mouse monoclonal antibody to dermcidin [G‐81]; Santa Cruz Biotechnology, Dallas, TX, USA) confirmed sweat leakage in the subpapillary dermis in the affected area (Fig. c,d) . In contrast, dermcidin was detected in the eccrine sweat duct and eccrine sweat glands but not in the dermis in the unaffected area (Fig.…”
Section: Case Reportmentioning
confidence: 99%